(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The rubber bushings are important components of automotive suspensions. These bushings play an important role in reducing noise and vibrations, enhancing ride comfort, and ensuring smooth vehicle motion. Therefore, investigating their elastic is of significant interest. This article presents the results of a force/torque analysis conducted on rubber bushings used in MacPherson and double wishbone front independent suspensions. To achieve this, three-dimensional geometric models of the rubber bushings were created using the SolidWorks software, employing two types of passenger cars as prototypes. The results were determined through Finite Element Analysis (FEA), and the radial force for all bushings was experimentally measured. The obtained results were then compared for validation.